Barriers and enablers that influence sustainable interprofessional education: a literature review. Issue 4 (July 2014) - Lawlis, Tanya Rechael; Anson, Judith; Greenfield, David
Abstract The effective incorporation of interprofessional education (IPE) within health professional curricula requires the synchronised and systematic collaboration between and within the various stakeholders. Higher education institutions, as primary health education providers, have the capacity to advocate and facilitate this collaboration. However, due to the diversity of stakeholders, facilitating the pedagogical change can be challenging and complex, and brings a degree of uncertainty and resistance. This review, through an analysis of the barriers and enablers investigates the involvement of stakeholders in higher education IPE through three primary stakeholder levels: Government and Professional, Institutional and Individual. A review of eight primary databases using 21 search terms resulted in 40 papers for review. While the barriers to IPE are widely reported within the higher education IPE literature, little is documented about the enablers of IPE. Similarly, the specific identification and importance of enablers for IPE sustainability and the dual nature of some barriers and enablers have not been previously reported. An analysis of the barriers and enablers of IPE across the different stakeholder levels reveals five key "fundamental elements" critical to achieving sustainable IPE in higher education curricula.